Reverberant shear wave fields and estimation of tissue properties - Parker, K.J.; Ormachea, J.; Zvietcovich, F.; Castañeda, B. (Institute of Physics, 2017)
The determination of shear wave speed is an important subject in the field of elastography, since elevated shear wave speeds can be directly linked to increased stiffness of tissues. MRI and ultrasound scanners are frequently used to detect shear waves and a variety of estimators are applied to calculate the underlying shear wave speed. The estimators can be relatively simple if plane wave behavior is assumed with a known direction of propagation. However, multiple reflections from organ boundaries and internal inhomogeneities and mode conversions can create a complicated field in time and space. Thus, we explore the mathematics of multiple component shear wave fields and derive the basic properties, from which efficient estimators can be obtained. We approach this problem from the historic perspective of reverberant fields, a conceptual framework used in architectural acoustics and related fields. The framework can be recast for the alternative case of shear waves in a bounded elastic media, and the expected value of displacement patterns in shear reverberant fields are derived, along with some practical estimators of shear wave speed. These are applied to finite element models and phantoms to illustrate the characteristics of reverberant fields and provide preliminary confirmation of the overall framework.
Keywords: Shear (geology); Estimator; Acoustics; Shear waves; Plane wave; Physics; Mechanics; Computer science; Mathematical analysis; Mathematics; Geology; Optics; Statistics; https://purl.org/pe-repo/ocde/ford#1.03.07